(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The article is devoted to a comparative legal study of the regulation of personal data processing in the hotel business of Uzbekistan. It examines the provisions of national legislation, including the Law "On Personal Data," and compares their practical application with international experience. The research analyzes key principles of data processing, issues of obtaining client consent, and requirements for customer notification. Special attention is given to data protection challenges and the specifics of transferring information to third parties. Based on the analysis, recommendations are proposed to improve national legal regulation and enhance information security in the hotel sector.